DIGITAL COMPETENCES OF SCHOOL LEADER: A SYSTEMATIC REVIEW - Thi Mai Huong, Vu; Thi Quy, Trinh (HNUE Journal of Science: Journal of Educational Science, 2025)
In recent years, Information and Communication Technologies (ICT) have played a significant role in enhancing the quality of life. However, their integration and potential in the field of education remain in a developmental phase. In this context, the present study conducts a systematic review of the literature on the digital competence of school leaders from 2015 to 2024. The primary objective is to identify prevailing research trends and suggest potential directions for future inquiry. The review methodology follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. After applying inclusion, exclusion, and thematic relevance criteria to studies indexed in the Scopus database, a total of 24 publications were selected for analysis. The findings reveal that digital competence is a multidimensional construct encompassing strategic, pedagogical, technical, and ethical components. Competent digital leaders play a vital role in fostering teacher development, managing innovation, and aligning technology use with institutional goals. However, disparities in context, limited empirical studies from under-resourced regions, and fragmented frameworks remain persistent challenges. The review concludes by recommending future research to develop adaptable competence models, investigate emerging technologies such as AI in leadership, and evaluate the long-term effects of digital leadership practices.